COVID-19 as a Potential Trigger for Immune Thrombotic Thrombocytopenic Purpura and Reason for an Unusual Treatment: A Case Report - Schwaegermann, Marie-Kristin; Hobohm, Lukas; Rausch, Johanna; Reuter, Michael; Griemert, Thomas-Friedrich; Sivanathan, Visvakanth; Falter, Tanja; Sprinzl, Martin F.; Lackner, Karl J.; Galle, Peter R.; Konstantinides, Stavros; Theobald, Matthias; von Auer, Charis (Hämostaseologie, 2021)
Immune thrombotic thrombocytopenic purpura (iTTP) is a rare autoimmune disorder characterized by severely reduced activity of the von Willebrand factor (VWF)-cleaving protease ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) due to autoantibodies. This leads to the development of pathogenic multimers of VWF, causing a thrombotic microangiopathy with decreased number of platelets, hemolysis, and life-threatening tissue ischemia of mostly brain, heart, and kidneys. Standard treatment of iTTP involves daily plasma exchange to remove ultra large multimers of VWF, inhibitors, substituting ADAMTS13, and the accompaniment of an immunosuppressive treatment with steroids. Recently, caplacizumab was approved for iTTP. Caplacizumab is a nanobody binding the A1 domain of VWF, blocking its interaction with glycoprotein Ib–IX–V platelet receptor and therefore preventing platelet aggregation. VWF activities may serve as therapeutic drug monitoring of caplacizumab, whereas ADAMTS13 activities may be used for biomarkers to guide caplacizumab treatment modalities and overall treatment duration. Additional immunosuppressive treatment by inhibiting autoantibody formation (e.g., the use of Rituximab, a chimeric monoclonal antibody directed against the B-cell antigen CD20) is a further treatment option. Infections are well-known causes for an acute episode for patients with iTTP. The novel SARS-CoV-2 virus is mainly associated with acute respiratory distress as well as diffuse endothelial inflammation and increased coagulopathy. However, little is known about an infection with SARS-CoV-2 virus triggering iTTP relapses. We herein report the case of an acute iTTP episode accompanying a SARS-CoV-2 infection.
Keywords: COVID-19; thrombotic thrombocytopenic purpura; caplacizumab